Localization of Disconnection Faults in PV Installations Using the Multiple Frequencies Injection Method - Jae-Sub Ko; Dae-Kyong Kim (Energies, 2021)
This paper proposes a method to detect disconnection faults and their exact location in PV systems. The proposed method injects multiple frequencies into a PV system with a transmitter and detects the injected signal using a receiver. The signal detected by the receiver exhibits different frequency characteristics on a disconnection failure. Based on this characteristic, a disconnection failure can be detected. In addition, by detecting the frequency radiated through the disconnection point, the exact disconnection point can be detected.